FLATULENCE - SYMPTOMS, TREATMENT (Proceedings of International Educators Conference, 2024)
Abdominal rest, flatulence (Greek: метеорисмос - rise up, rest) is the relaxation of the stomach and the increase in the formation of gas in the intestines. In healthy people, the cause of such a disorder may be a specific diet or a tendency to constipation: the food that enters the body is retained in the intestines, leading to decay processes, resulting in gas. The formation of a large amount of gas can indicate the development of the disease.Information about abdominal rest